Water-in-Fluorous Solvent Microemulsions Media for (Bio)molecular Solvation - Deepika (Langmuir : the ACS journal of surfaces and colloids, 2025)
Evidence for the formation of stable water pools within fluorous solvents (perfluorodecalin, perfluoromethylcyclohexane, and perfluorooctane) facilitated by a perfluorinated emulsifier perfluoroheptanoic acid (PFHA) under ambient conditions is presented. The presence of water-in-fluorous solvent (w/fluorous) microemulsions (MEs) is initially established with visual inspection and by constructing a pseudo-ternary phase diagram followed by dynamic light scattering (DLS), small-angle X-ray scattering (SAXS), and FTIR absorbance data analysis. DLS and SAXS measurements show that the hydrodynamic diameter (Dh) and radius of gyration (Rg) increase significantly with increase in water content. The spherical model of fitting is found to be the most accurate in Guinier analysis, suggesting the MEs to be spherical in shape. FTIR absorbance spectral deconvolution reveals a decrease and increase in the relative population of bound and bulk-like water, respectively, as the water content is increased within the system. Solute solvation within w/fluorous MEs was investigated utilizing several structurally different (bio)molecular probes possessing varying optical spectroscopic signatures. Rotational reorientation times recovered from the excited-state fluorescence anisotropy decay indicate a decreasing trend with increasing water content, suggesting transport of rhodamine 6G and fluorescein Na salt from bulk media to the water pools where they are preferentially solvated. Excited-state proton transfer (ESPT) for pyranine and (-)-riboflavin also reveals the solvation of these probes within ME water pools. A common porphyrin, meso-tetrakis(4-sulfonatophenyl)porphyrin, readily undergoes J aggregation within the water pools. Protein, bovine serum albumin, preferentially solubilizes within the water pools of the w/fluorous MEs and effectively interacts with the pH indicator bromophenol blue. This w/fluorous ME medium with fluorous solvent as the bulk phase is bound to play a major role in the pulmonary drug delivery process and has potential to completely replace conventional VOC-based MEs across all applications